CONDENSATION REACTIONS OF 1,3-DIPHENYL-2-PROPEN-1-0NES WITH NUCLEOPHILIC REAGENTS (Biological Sciences - PJSIR, 2022)
The reactivity of substituted I,3-diphenyl-2-propen-l- ones has been investigated under acidic and basic conditionswith amino-compounds resulting to heterocyclic derivatives. Other reactions with ethyl acetoacetate and acetylacetonehave afforded substituted 3,S-disphenylcyclohexenones.